Spelling and Use of Words that are Translated from Other Languages into German - Berdimurodov Adham Musurmonovich (Zien Journals, 2022)
German, considered one of the languages of Western Europe, has also enriched its vocabulary over the years based on words and phrases derived from the languages of neighboring countries, including ancient Latin, as well as Italian, French, Spanish, Russian, and English. While the vocabulary of latin took the lead during the early stages of german development, it is noteworthy that during the 9th and 13th centuries, words and phrases from French and Spanish, Italian during the Awakening in Europe, Russian as a result of World War II, and English played a key role in the vocabulary of the German language.
Keywords: Job; jobben; Computer; Lyceum